Reading comprehension of narrative texts through the use of digital storytelling in social networks: a systematic review (Revista de Investigaciones Universidad del Quindío, 2023)
Introduction: The article is structured in a review of the literature, to know what has been done with the subject and what aspects still remain to be studied. Objective: to analyze research carried out on the comprehension of narrative texts through the use of digital storytelling in social networks in secondary school students through a systematic review. Material and methods: it consisted of a succession of steps for the bibliographical and scientific review of master's degree and specialization research projects based on the methodology of Manchado et al. (2009) on exploratory systematic reviews. Results: Storytelling is a didactic resource that allows motivating, activating attention and generating participation and interaction in students. Conclusions: digital storytelling is not yet associated with reading comprehension; therefore, it is a pending duty in research in the area of ​​Spanish and literature.
Keywords: Exploratory systematic review; reading comprehension; digital storytelling; narrative texts; social networks